2007
DOI: 10.1111/j.1462-5822.2006.00783.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia attachment to mammalian cells requires protein disulfide isomerase

Abstract: SummaryFor Chlamydia, an intracellular pathogen of humans, host cell invasion is obligatory for survival, growth and pathogenesis. At the molecular level, little is known about the binding and entry of Chlamydia into the mammalian host cell. Chlamydia are genetically intractable therefore experimental approaches targeting the host are often necessary. CHO6 is a mutagenized cell line resistant to attachment and infection by Chlamydia. In this study, CHO6 was shown using proteomic methods to have a defect in pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 54 publications
1
56
0
Order By: Relevance
“…In parasites such as Neospora caninum and Toxoplasma gondii, PDI was reported as playing a role in the parasite-host cell interaction (Liao et al 2006;Robinson and Roy 2006). Moreover, it has recently been shown that native PDI on the cell surface is required for the effective attachment of Chlamydia, an obligate intracellular bacterial pathogen of eukaryotic cells (Conant and Stephens 2007). Likewise, a 52-kDa PDI of N. caninum techyzoites is involved in the adhesion of parasites to host cells (Naguleswaran et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In parasites such as Neospora caninum and Toxoplasma gondii, PDI was reported as playing a role in the parasite-host cell interaction (Liao et al 2006;Robinson and Roy 2006). Moreover, it has recently been shown that native PDI on the cell surface is required for the effective attachment of Chlamydia, an obligate intracellular bacterial pathogen of eukaryotic cells (Conant and Stephens 2007). Likewise, a 52-kDa PDI of N. caninum techyzoites is involved in the adhesion of parasites to host cells (Naguleswaran et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Using chemical mutagenesis, Carabeo et al (8) isolated a CHO cell clone resistant to Chlamydia, and Fudyk et al (9) found 12 CHO clones that are resistant to Chlamydia, but had difficulty identifying the mutations that impart resistance. Only one of the 12 clones initially identified was subsequently characterized as carrying a mutation in protein disulfide isomerase (10). Chemical mutagenesis screens suffer from the fact that a great many genes will be altered because of the dose of mutagen required to obtain a pool of mutants that can be screened.…”
mentioning
confidence: 99%
“…During EB attachment, exposure of HEC-1B cells to three different inhibitors of PDI reductive activity (DTNB, bacitracin, and anti-PDI antibodies) resulted in reduced chlamydial infection. Subsequently, a proteomic study of CHO6 cell line [121], a mutagenized cell line resistant to attachment and infection by Chlamydia, showed that CHO6 has a defect in processing of the leader sequence of PDI, which results in altered cellular distribution of PDI. PDI is abundantly localized in the ER, and surface localization is predominantly sequestered to large patches compared to the punctate pattern in the wild type CHOK1 cells.…”
Section: Pathogenic Bacteria: Chlamydia Entrymentioning
confidence: 99%